Reshaping financial systems. New technologies and financial innovations - Evidence from the United States, Mexico and Brazil - Ewa Lechman; Adam Marszk (Gdańsk University of Technology, Faculty of Management and Economics, 2014)
The paper unveils whether ICT diffusion determines development of financial innovation in emerging economies. Particularly, we examine the impact of ICT adoption on changing values of exchange traded funds in Brazil and Mexico, comparing it to the United States as reference country (benchmark). Our methodological framework includes descriptive statistics, logistic growth models (used to estimate ETFs growth) and generalized linear models (used to check for relationship between ICT adoption and ETFs value). In each case we run country-specific estimates. Data on ICT adoption (approximated by Internet Users and Fixed Broadband Subscriptions) are exclusively derived from World Telecommunication/ICT Indicators Database 2012 (16th edition), and exchange traded funds from funds' providers and reports published by BlackRock. Analysis period is set for 2000-2012. Empirical findings collectively conclude that in all three countries, growth of ICT was pervasive, and this was accompanied by fast development of exchange traded funds in Mexico and in the United States, measured by increases in assets under management. Moreover, in the period 2002-2012 Mexico has caught up with the United States in terms of ETFs share in total investment funds (sum of assets of ETFs and mutual funds). In Brazil, even though ETFs growth rates were high, in 2012 share of ETFs in investment funds remained at a relatively lower level of 0.17%. Additionally, the relationship between ICT adoption and ETFs development was reported as strong, positive and statistically significant in each of analyzed countries.
Keywords: G11; G23; O16; O33; O57; 330; emerging markets; ICT; ETFs